The oculoauriculovertebral spectrum: Refining the estimate of birth prevalence - Gabbett, Michael T. (Journal of Pediatric Genetics, 2012)
The oculoauriculovertebral spectrum (OAVS) is a well-described pattern of congenital malformations primarily characterized by hemifacial microsomia and/or auricular dysplasia. However, the birth prevalence of OAVS is poorly characterized. Figures ranging from 1 in 150,000 through to 1 in 5,600 can be found in the literature – the latter figure being the most frequently quoted. This study aims to evaluate the reasons behind such discrepant figures and to refine the estimated birth prevalence of OAVS. Published reports on the incidence and prevalence of OAVS were systematically sought after. This evidence was critically reviewed. Data from appropriate studies was amalgamated to refine the estimate of the birth prevalence for OAVS. Two main reasons were identified why birth prevalence figures for OAVS are so highly discrepant: differing methods of case ascertainment and the lack of a formal definition for OAVS. This study refines the estimate of birth prevalence for OAVS to between 1 in 40,000 and 1 in 30,000. This number needs to be confirmed in a large well-designed prospective study using a formally agreed-upon definition for OAVS.
Keywords: Incidence; prevalence; oculoauriculovertebral; syndrome; Goldenhar syndrome